2008
DOI: 10.3386/w14174
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Physician Human Capital: Analyzing Patients Randomized to Physician Teams

Abstract: for helpful comments and insights. We also greatly benefited from the efficient programming of Andrew Siroka. All remaining errors are our own. The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similarly,Currie et al (2016) find that cardiologists who use invasive procedures for heart attacks more frequently have better outcomes.5 This finding is also consistent withDoyle et al (2010), who find that patients randomly assigned to the physician team from the higher-ranked residency program incurred lower costs and indistinguishable outcomes from those assigned to the team from the lower-ranked program.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Similarly,Currie et al (2016) find that cardiologists who use invasive procedures for heart attacks more frequently have better outcomes.5 This finding is also consistent withDoyle et al (2010), who find that patients randomly assigned to the physician team from the higher-ranked residency program incurred lower costs and indistinguishable outcomes from those assigned to the team from the lower-ranked program.…”
supporting
confidence: 55%
“…Our paper contributes primarily to two recent literatures. One literature has leveraged the quasi-random assignment of patients to hospitals and physician groups in order to evaluate different aspects of physician practice style and resource use across different healthcare settings (see, e.g., Epstein and Nicholson, 2009;Doyle et al, 2010Doyle et al, , 2014Currie et al, 2016;Currie and MacLeod, 2017). Our study uses similar identifying variation to this literature and has overlapping goals.…”
Section: Introductionmentioning
confidence: 99%
“…The number of procedures is another measure of treatment intensity, while the likelihood of receiving treatment within 1 day could reflect quality in that delays may be associated with treatment by less‐qualified physicians (Doyle, Ewer, and Wagner ), overcrowding, or understaffing. Inpatient mortality is the final outcome measure.…”
Section: Methodsmentioning
confidence: 99%
“…Even if a particular physician is absent during a month, the characteristics of the physicians on the team in the unit do not vary on a month to month basis because patients are cared for by other members of the physician's team and practice styles within physician groups tend to be homogeneous (Wennberg and Gittlesohn 1973). More recent work by Doyle, Ewer, and Wagner (2010) demonstrated that patient outcomes in the VA were invariant to physician team assignment. 9 Outside of the VA, Medicare pays a fixed amount based on the patient's admitting diagnosis.…”
mentioning
confidence: 99%